Obesity is Associated with Primary Infertility in Women of Childbearing Age - Muji Lestari; Weni Guslia Refi; Maya Dika Dahliana; Tesya Oktavia; Gita Nirmala Sari (Universitas Andalas, 2023)
Infertility problems can have a big impact on married couples who experience them, apart from causing medical problems, infertility can also cause economic and psychological problems. From 2020 data at the research place, as many as 206 (20.15%) women of childbearing age experienced primary infertility and as many as 43 women of childbearing age (20.87%) experienced obesity. This study aims to analyze the association between obesity and primary infertility in women of childbearing age. The method used in this research is quantitative with a cross-sectional approach. The sample of this study was 840 women of childbearing age who visited the infertility clinic in 2021. The results showed that there was a significant association between obesity and the incidence of primary infertility at with the P value <0.001. This is very important to prevent obesity in women of childbearing age to avoid primary infertility